Membangun Demokrasi melalui Profesionalisme Tentara Nasional Indonesia - Yusa Djuyandi (Humaniora, 2012)
Democratic development for more than 14 years was seen walking "back and forth", one reason is the slow process of the professionalism of the Indonesian National Army (TNI). In history, that the lack of military professionalism has resulted in the birth of military force against civilians, and military involvement in politics, it ultimately undermined democracy that aims to strengthen civil society. The purpose of this study is to describe and analyze the process of democratic development through the realization of military professionalism. The research method used was qualitative method through the use of primary data (observations and interviews) and secondary data (media and documents). Democratic development aims to generate social and political conditions better, one that supports that effort is the creation of military professionalism. But today, it is appeared several groups trying to restore military strength in practical politics. Based on the discussion, the writer concludes that efforts to build democracy in Indonesia met with resistance. This is due to the persistence of the effort to bring the military back into the world of practical politics.